2014
DOI: 10.1177/0954406214564411
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elastic/plastic buckling analysis of thick/thin skew plates under uniaxial and biaxial loading

Abstract: In this study, elastic/plastic buckling analysis of thick skew plates subjected to uniaxial compression or biaxial compression/tension loading using the generalized differential quadrature method is presented for the first time. The governing differential equations are derived based on the incremental and deformation theories of plasticity and first-order shear deformation theory. The elastic/plastic behavior of the plates is described by the Ramberg–Osgood model. Generalized differential quadrature discretiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Xiong and Wang 11 studied both the vibration and stability of a non-conservative two-degree-of-freedom system. Nonlinear elastic and plastic buckling analysis of thick skew plates under uniaxial and biaxial loadings were studied by Maarefdoust and Kadkhodayan 12 using the generalized differential quadrature method (DQM). Wang et al 13 proposed a modified version of the DQM for analyzing the static buckling of different skew plates.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong and Wang 11 studied both the vibration and stability of a non-conservative two-degree-of-freedom system. Nonlinear elastic and plastic buckling analysis of thick skew plates under uniaxial and biaxial loadings were studied by Maarefdoust and Kadkhodayan 12 using the generalized differential quadrature method (DQM). Wang et al 13 proposed a modified version of the DQM for analyzing the static buckling of different skew plates.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that predictions of DT and IT are close to each other if the small deformation assumption is not violated. Maarefdoust and Kadkhodayan 30,31 suggested the use of generalized DQ (GDQ) method for addressing the nonlinear elastoplastic buckling problem of skew plates. By means of the same solution technique and based on both DT and IT, the elastic-plastic buckling analysis of plates made of functionally graded materials was presented in BeikMohammadlou and EkhteraeiToussi.…”
Section: Introductionmentioning
confidence: 99%